Analisis peran guru dalam menerapkan sikap tanggung jawab siswa pada pembelajaran ppkn materi hak, kewajiban, dan tanggung jawab di sekolah dasar - Dyah Sulistyo Wati; Hasan Mahfud; Dwi Yuniasih Saputri (Universitas Sebelas Maret, 2021)
This research goals were to described the role of teachers in implementing student responsibility attitudes in Civic Education learning on rights, obligations, and responsibilities. This research used descriptive qualitative research with the research subjects of fifth grade teachers and fifth grade students of SD Negeri Tegalrejo No. 98. The data collection was cloned by observation, interviews, and documentation. The data obtained were then analyzed consisting of three components, namely data reduction, data presentation, and drawing conclusions. The results showed that the teacher's role in implementing an attitude of responsibility that is seen in implementing the attitude of student responsibility was the role of the teacher as a motivator when the teacher inspires students that learning was aimed at gaining achievement, inviting students to be active in learning, providing reinforcement, arousing student interest. The teacher's role as a facilitator when the teacher provides online learning, makes it easy to collect assignments, improves IT skills. The teacher's role as an evaluator when the teacher makes rules in doing assignments, conducts evaluations at each meeting, and corrects student answers.